P4.008 Relating Multilevel Psychosocial Constructs with Risky Sex Among Men Who Have Sex with Men (MSM) and Male-To-Female Transgender Women (TW) in Peru. (13th July 2013) - Konda, K A; Silva-Santisteban, A; Maiorana, A; Pollack, L; Salazar, X; Caceres, C F; Kegeles, S M
Abstract : Background: Risk for HIV/STIs is high among gay men (GM) and male-to-female transgender women (TW) and understanding the underlying reasons for risk is essential for planning effective interventions. Few instruments have been developed to examine psychosocial constructs for Spanish-speaking Latin American GM/TW. Methods: We developed scales to measure psychosocial constructs and then conducted a survey to assess their association with risky sex among Peruvian GM/TW (Cronbach alphas ranged from 0.66 to 0.85). We explored constructs at the: (1) individual-level (e.g. experiences of homophobia, belief in one's capability to have safer sex), (2) social-level (e.g. social norms about safer sex, social support) and (3) community level (valuing being a part of the gay/trans community). We used student's t-tests to explore the association between these constructs and risky unprotected anal intercourse (UAI), defined as UAI in the past 2 months with non-primary partners or primary partners who are serodiscordant or serostatus unknown, non-monogamous, or who have been a primary partner for less than 6 months. Results: We surveyed 247 MSM/TW with a mean age of 31.3 (standard deviation 8.2), 200 were GM and 47 were TW. Risky UAI was reported by 18.6% of GM/TW. GM/TW reporting risky UAI also reported significantly lower social support, feeling less capable of having safer sex, having sex in challenging contexts more often, and more experiences of homophobia/transphobia. Each of these constructs were significantly associated with reporting risky UAI with a male partner (all p-values < 0.05). Other scales were not associated with risky UAI. Conclusions: The psychosocial scales performed well among GM/TW and several were significantly associated with risky UAI. Constructs at the individual and social level were associated with risky UAI, suggesting that multilevel HIV/STI prevention interventions with this population may be more valuable than individual-level interventions.